2015
DOI: 10.1063/1.4930274
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of water film adsorbed on mica surfaces

Abstract: The structure profiles and physical properties of the adsorbed water film on a mica surface under conditions with different degrees of relative humidity are investigated by a surface force apparatus. The first layer of the adsorbed water film shows ice-like properties, including a lattice constant similar with ice crystal, a high bearing capacity that can support normal pressure as high as 4 MPa, a creep behavior under the action of even a small normal load, and a character of hydrogen bond. Adjacent to the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
7
24
0
Order By: Relevance
“…The skin viscosity increases from 0.007 to 0.019 ×10 -2 mN·s/m 2 , agreeing with the trend of measurements [6]. Theoretical reproduction of the stress thermal decay of water skin, derived the DL = 192 K and the EL = 0.095 eV [101,47].…”
supporting
confidence: 75%
“…The skin viscosity increases from 0.007 to 0.019 ×10 -2 mN·s/m 2 , agreeing with the trend of measurements [6]. Theoretical reproduction of the stress thermal decay of water skin, derived the DL = 192 K and the EL = 0.095 eV [101,47].…”
supporting
confidence: 75%
“…Numerous studies 2,6,7,[12][13][14][15]17,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] have examined the behaviour of nano-confined aqueous solutions in various systems and under different circumstances. Experimentally, the two main approaches are based on the surface force apparatus (SFA) and atomic force microscopy (AFM) with each family of methods offering different modes of operation.…”
Section: Introductionmentioning
confidence: 99%
“…22,28,31,33,[38][39][40][41] The distance between the confining surfaces can be measured in an absolute manner using interferometry, and dynamical measurements of the viscoelastic properties of confined aqueous solutions are possible over a range of frequencies (typically 1-3 Hz) using surface force balances (SFB), 42 or SFA with resonance detection. 33,38,40,41 In contrast, AFM-based methods probe a small number of liquid molecules, typically located between a nanometre sharp tip and an atomically surface. 2,43,44 The exact confinement geometry is less well controlled, unless the tip radius is artificially increased.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao and co-workers [89] developed a surface force apparatus to detect the skin rigidity of the monolayer skin of the adsorbed water film on a mica surface under conditions with different degrees of relative humidity. They confirmed that the first layer of the adsorbed water film is ice-like, including a lattice constant similar with ice crystal, a high bearing capacity that can support normal pressure as high as 4 MPa, a creep behavior under the action of even a small normal load, and a character of hydrogen bond.…”
Section: Supersolid Skin Rigiditymentioning
confidence: 99%
“…Fig. 10.13 The force-distance relation for two mica sheets brought together at 298 K. Thin water films formed on each mica substrate by adsorption under 80 % relative humidity for 10 h. The repulsive force increases in two steps (inset) and it reaches a maximum of 2400 mN/m (4.0 MPa) at a separation of 7.3 Å (Reprinted with permission from [89].) Therefore, the experimental results confirmed that the high rigidity of the adsorbed water film exhibiting the supersolid nature-solid-like properties including low flow ability, water insolubility, high carrying capacity in normal direction (more than 4 MPa), and the low mass density, smaller size and larger separation of molecules.…”
Section: Supersolid Skin Rigiditymentioning
confidence: 99%